2016
DOI: 10.1016/j.celrep.2016.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Standardized Whole-Blood Transcriptional Profiling Enables the Deconvolution of Complex Induced Immune Responses

Abstract: Systems approaches for the study of immune signaling pathways have been traditionally based on purified cells or cultured lines. However, in vivo responses involve the coordinated action of multiple cell types, which interact to establish an inflammatory microenvironment. We employed standardized whole-blood stimulation systems to test the hypothesis that responses to Toll-like receptor ligands or whole microbes can be defined by the transcriptional signatures of key cytokines. We found 44 genes, identified us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
95
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 85 publications
(97 citation statements)
references
References 34 publications
1
95
0
1
Order By: Relevance
“…Additionally, our recent work has highlighted that in conditions of limiting dose of microbial stimulus, cytokines participate in the spreading of the inflammatory signal. Moreover, they report that the core cytokine-induced signatures are capable of capturing the variable response to stimulation by complex microorganisms (40). Together, our strategy enabled detailed analysis of the response to BCG with the demonstration that a diverse set of immune cells underlay what is a plastic and flexible inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, our recent work has highlighted that in conditions of limiting dose of microbial stimulus, cytokines participate in the spreading of the inflammatory signal. Moreover, they report that the core cytokine-induced signatures are capable of capturing the variable response to stimulation by complex microorganisms (40). Together, our strategy enabled detailed analysis of the response to BCG with the demonstration that a diverse set of immune cells underlay what is a plastic and flexible inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…An additional advantage of TruCulture is its adaptability to diverse immune stimuli and that the biological readout can be modified to monitor alterations in cellular phenotype, 12 induced protein secretion, 12 RNA expression changes, 13 and metabolic or lipidomic functional changes. Transcriptional analysis of stimulated whole blood can be challenging due to multiple technical reasons, but we have developed a high-throughput single-step RNA extraction method from stimulated TruCulture samples allied to a Nanostring hybridization array readout.…”
Section: Dissecting Signatures Of Induced Immune Responses For Correlmentioning
confidence: 99%
“…Transcriptional analysis of stimulated whole blood can be challenging due to multiple technical reasons, but we have developed a high-throughput single-step RNA extraction method from stimulated TruCulture samples allied to a Nanostring hybridization array readout. 13 Utilizing the diverse stimulation conditions applied to the Milieu Interieur cohort, we tested the hypothesis that the transcriptional signature of key effector cytokines can capture the responses to Toll-like Receptor (TLR) ligands or microbes. To do this we analyzed the expression of 572 genes in 25 healthy donors following stimulation with 4 key innate cytokines (IFN-β, IFN-γ, IL-1β, and TNF-α) applying unsupervised principal component analysis (PCA) and a linear support vector machine (SVM) algorithm.…”
Section: Dissecting Signatures Of Induced Immune Responses For Correlmentioning
confidence: 99%
See 1 more Smart Citation
“…Using this approach, the authors identified gene expression signatures that could predict the humoral immune response to the yellow fever vaccine. Similarly, several international projects, such as the Human Immunology Project consortium8 funded by National Institute of Health and the Health Human Project emanating from the Milieu Intérieur Consortium,9 have already revealed the power of multiparametric systems immunology studies 10…”
Section: Introductionmentioning
confidence: 99%